A dual target molecular magnetic resonance imaging probe for noninvasive profiling of pathologic alpha-synuclein and microgliosis in a mouse model of Parkinson’s disease - Sun, Xianwei; Badachhape, Andrew; Bhandari, Prajwal; Chin, Jeannie; Annapragada, Ananth; Tanifum, Eric (Frontiers in Neuroscience, 2024)
The pathogenesis of Parkinson's disease (PD) is characterized by progressive deposition of alphasynuclein (α-syn) aggregates in dopaminergic neurons and neuroinflammation. Noninvasive in vivo imaging of α-syn aggregate accumulation and neuroinflammation can elicit the underlying mechanisms involved in disease progression and facilitate the development of effective treatment as well as disease diagnosis and prognosis. Here we present a novel approach to simultaneously profile α-syn aggregation and reactive microgliosis in vivo, by targeting oligomeric α-syn in cerebrospinal fluid with nanoparticle bearing a Magnetic Resonance Imaging (MRI), contrast payload. In this proof-of-concept report we demonstrate, in vitro, that microglia and neuroblastoma cell lines internalize agglomerates formed by cross-linking the nanoparticles with oligomeric αsyn. Delayed in vivo MRI scans following intravenous administration of the nanoparticles in the M83 α-syn transgenic mouse line show statistically significant MR signal enhancement in test mice versus controls. The in vivo data were validated by ex-vivo immunohistochemical analysis which show strong correlation between in vivo MRI signal enhancement, Lewy pathology distribution, and microglia activity in the treated brain tissue. Furthermore, neuronal and microglial cells in brain tissue from treated mice display strong cytosolic signal originating from the nanoparticles, attributed to in vivo cell uptake of nanoparticle/oligomeric α-syn agglomerates.